(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Systemic lupus Erythrematosus disease (SLE), is an autoimmune multisystemic disease, and is associated with the considerable morbidity. The hematological abnormalities might be the initial indicator. Disease duration may have an impact on the hematological parameters. Method: This research has been conducted in the Renal Transplant Center, Medical City, Baghdad/Iraq. Total of 50 female patients, aged 31.15±9.11 years and 40 femals aged 35.10±10.92 as controls. Total counts of RBCs, WBCs, and ESR has been valued by automated hematology analyzer. Results: Results of ESR has been showen a significant increase (p<0.001) in patients with SLE as compaired with the control group. And a significant decrease in RBCs, WBCs counts (p<0.001) in SLE patients when compared with those of control. Correlation analysis for RBCs and WBCs has been showen a significant negative correlation with the duration of disease in patients with SLE, and positive correlation has been found between ESR and the duration of disease. Conclusion: RBCs and WBCs has been changed in SLE patients, and they were related to the duration of disease.